KONTRIBUSI KETERAMPILAN MENYIMAK DONGENG TERHADAP KETERAMPILAN MENULISKAN KEMBALI DONGENG - Arini, Hilda; Nursaid, Nursaid; Ratna, Ellya (Universitas Negeri Padang, 2016)
ABSTRACTÂ This article is aim to find out the contribution between listening skills on the story to the re-write skill on the story by the student on SMP N 1 Kinali West Pasaman. The research conducted by quantitative and descriptive method. There were three results of research conducted by the were (1) the listening skill of students can be clasified into good enough that is 72,45 %, (2) the re-write skill of students can be clasified into good enough that is 72,34% and (3) the listening skill give more contribution to the students in by the second grade studentsÂ SMP N 1 Kinali West Pasaman in re-write the story, that is in 92,2%. In conclusion, listening skill is really needed in re-write the story skill.Â Kata kunci: kontribusi, menyimak, menuliskan kembali, dongeng